Exploring the Impact of Galaxy Interactions over Seven Billion Years with CAS - Miller, S; Jogee, S; Conselice, C; Penner, K; Bell, E; Zheng, X; Papovich, C; Skelton, R; Somerville, R; Rix, H; Barazza, F; Barden, M; et al. (2008)
We explore galaxy assembly over the last seven billion years by characterizing "normal" galaxies along the Hubble sequence, against strongly disturbed merging/interacting galaxies with the widely used CAS system of concentration (C), asymmetry (A), and 'clumpiness' (S) parameters, as well as visual classification. We analyze Hubble Space Telescope (HST) ACS images of ~4000 intermediate and high mass (> 10^9 solar masses) galaxies from the GEMS survey, one of the largest HST surveys conducted to date in two filters. We explore the effectiveness of the CAS criteria [A>S and A>~0.35] in separating normal and strongly disturbed galaxies at different redshifts, and quantify the recovery and contamination rate. We also compare the average star formation rate and the cosmic star formation rate density as a function of redshift between normal and interacting systems identified by CAS.